ТЕОРЕМЫ О ГОЛОМОРФНОСТИ ФУНКЦИЙ, ПРЕДСТАВИМЫХ ИНТЕГРАЛОМ БОХНЕРА-МАРТИНЕЛЛИ - Отемуратов, Б.П.; Джумабаев, Д.Х. (SCIENCE and SOCIETY, 2021)
An analogue of the Hartogs-Bochner theorem is proved. Theorems on the holomorphism of functions represented by the Bochner-Martinelli integral are obtained for continuous functions in areas with fragmentary smooth boundaries.
Keywords: Bochner-Martinelli integral; holomorphism of functions; area with a smooth boundary